Relationship of Prior Knowledge and Scenario Quality With the Effectiveness of Problem-based Learning Discussion among Medical Students of Universitas Malikussaleh, Aceh, Indonesia - Sri Rahayu, Mulyati; Wahyuni, Sri; Yuziani, Yuziani (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Problem-Based Learning (PBL) is a student-centred learning approach that employs clinical case scenarios to trigger learning and is conducted in small group discussions. The familiarity and prior knowledge of the students with the problem affect and stimulate student discussion in the tutorial group. Effective discussion ensures successful PBL learning. This study aimed to determine the relationship between prior knowledge and the scenario quality with the effectiveness of the PBL discussions. Methods: This cross-sectional study was conducted in 2021 and involved 89 undergraduate medical students in the learning of the Immunology and Neoplasm module at the Faculty of Medicine of Universitas Malikussaleh. The Quality of PBL Problem Questionnaire and the Tutorial Group Effectiveness Instrument (TGEI) Questionnaire were used for data collection. The GPAs of the students were obtained as prior knowledge data. The data were analysed using the Chi-square test with a significant level of 0.05. Results: Most of the students had good prior knowledge (51.2% vs 47.8%). The results did not show a significant correlation between prior knowledge and the scenarios with the discussion effectiveness in the PBL group (p = 0.154 and 0.871, respectively). Conclusion: This study suggests that prior knowledge did not affect the effectiveness of discussions within the tutorial groups. Our study discovered a non-significant relationship between the scenario quality and the effectiveness of PBL discussions; however, our data revealed that good scenarios mostly led to effective tutorial group discussions. References: Wood D. Problem based learning. BMJ. 2003;326:328-30. https://doi.org/10.1136/bmj.326.7384.328 Dolmans D, Grave D, Wolfhagen W, Van Der Vleuten I, C. Problem-based learning: future challenges for educational practice and research. Med Educ. 2005;39:732-41. https://doi.org/10.1111/j.1365-2929.2005.02205.x Singaram V, Van Der Vleuten C, Berkel V, Dolmans H, D. Reliability and validity of a Tutorial Group Effectiveness Instrument. Med Teach. 2010;32:e133-e137. https://doi.org/10.3109/01421590903480105 Visschers-Pleijers A, Dolmans D, Wolfhagen I, Van Der Vleuten C. Development and validation of a questionnaire to identify learning-oriented group interactions in PBL. Med Teach. 2005;27:701-10. https://doi.org/10.1080/01421590500046395 Dolmans D, Schmidt H. What do we know about cognitive and motivational effects of small group tutorials in problem-based learning?. Adv Health Sci Educ Theory Pract. 2006;11:321-36. https://doi.org/10.1007/s10459-006-9012-8 Henk G, Schmidt D, Dolmans, Wim H, Gijselaers, Jacques E, Marchais. Theoryguided design of a rating scale for course evaluation in problem-based curricula. Teaching and Learning in Medicine. 1995;7:82-91. https://doi.org/10.1080/10401339509539719 Soppe M, Schmidt H, Bruysten R. Influence of problem familiarity on learning in a problembased course. Instr Sci. 2005;33:271-81. https://doi.org/10.1007/s11251-004-7688-9 Azer S. Becoming a student in PBL course: twelve tips for successful group discussion. Med Teach. 2004;26:12-5. https://doi.org/10.1080/0142159032000156533 Dolmans D, Snellen-Balendong H, Wolfhagen H, I, Der Vleuten V, C. Seven principles of effective case design for a problem-based curriculum. Med Teach. 1997;19:185-9. https://doi.org/10.3109/01421599709019379 Sianipar I, Himanto D, Siregar I, Husin F, Sutedja E, Sukandar H. Hubungan Kinerja Tutor dan Kualitas Kasus Skenario Terhadap Keefektifan Kelompok Pada Metode Belajar Problem Based Learning. Indonesia Journal Education and Midwifery Care (IJEMC. 2016;3:1-7. https://doi.org/10.24198/ijemc.v3i2 Sockalingam N, Rotgans J, Schmidt H. Student and tutor perceptions on attributes of effective problems in problem-based learning. High Educ. 2011;62:1-16. https://doi.org/10.1007/s10734-010-9361-3 Academic Guidelines of Faculty of Medicine Universitas Malikussaleh / Panduan Akademik Prodi. 2020;. Martina G. Hubungan prior knowledge terhadap keefektifan kelompok pada metode belajar problem based learning di program studi D3 Kebidanan STIK Immanuel. Health Science Growth ( HSG ) Journal. 2016;1:1-12. Abdalla M, Eladl M. Student perception of the effect of problem familiarity on group discussion quality in a problem-based learning environment. GMS J Med Educ. 2019. 2019 May 16;36:29. https://doi.org/10.3205/zma001237 Sandaria F, Sulistiawati, Purnamasari B. The Relationship of Scenario Quality With the Effectiveness of Seven Jumps Problem-Based Learning Discussion on Medical Students of Mulawarman University. Jurnal Ilmu Kesehatan. 2021;9:137-41. https://doi.org/10.30650/jik.v9i2.2257 Keshk L, El-Azim S, Qalawa S. Quality of Problem Based Learning Scenarios at College of Nursing in Egypt and KSA: Comparative Study. American Journal of Educational Research. 2016;. https://doi.org/10.12691/education-4-9-10 Van Blankenstein F, Dolmans D, Van Der Vleuten C, Schmidt H. Relevant prior knowledge moderates the effect of elaboration during small group discussion on academic achievement. Instr Sci. 2013;41:729-44. https://doi.org/10.1007/s11251-012-9252-3 Munshi F, Sayed E, El, Dolmans D. Development and utility of a questionnaire to evaluate the quality of PBL problems. South East Asian Journal of Medical Education. 2008;2:32-40. https://doi.org/10.4038/seajme.v2i2.481 Slavin R. Research on Cooperative Learning and Achievement: What We Know, What We Need to Know. Contemp Educ Psychol. 1996;21:43-69. https://doi.org/10.1006/ceps.1996.0004 Mewo Y, Manoppo F, Wungouw H. Evaluasi kualitas skenario Problem-Based Learning di Fakultas Kedokteran Universitas Sam Ratulangi. Jurnal e-Biomedic. 2018;6:90-5. https://doi.org/10.35790/ebm.6.2.2018.20967 Singaram V, Van Der Vleuten C, Berkel V, Dolmans H, D. Reliability and validity of a Tutorial Group Effectiveness Instrument. Med Teach. 2010;32:e133-e137. https://doi.org/10.3109/01421590903480105 Shankar P, Nandy A, Balasubramanium R, Chakravarty S. Small group effectiveness in a Caribbean medical school’s problem-based learning sessions. J Educ Eval Health Prof. 2014. 2014 Mar 24;11. https://doi.org/10.3352/jeehp.2014.11.5 Norman G, Schmidt H. Revisiting ‘Effectiveness of problem-based learning curricula: theory, practice and paper darts’. Medical Education. 2016;50:793-7. https://doi.org/10.1111/medu.12800 Istadi Y, Harsono, Prabandari Y. Faktor-faktor yang dianggap sebagai prediktor terhadap keefektifan kelompok tutorial Problem Based Learning (PBL). Jurnal Pendidikan Kedokteran Indonesia. 2012;1:59-67. https://doi.org/10.22146/jpki.25130 Hamidy M, Asni E. Faktor-faktor yang Mempengaruhi Partisipasi Mahasiswa dalam Proses Tutorial pada Metode Belajar Problem-Based Learning (PBL) di Fakultas Kedokteran Universitas Riau. Journal of Medical Science. 2017;4:30-5. https://doi.org/10.26891/JIK.v4i1.2010.30-35 Susanti P, Lisiswanti R, Soleha T, Saputra O, Okyafany. Hubungan Kualitas Skenario Terhadap Keefektifan Diskusi Problem-Based Learning (PBL) Blok Emergency Pada Mahasiswa Fakultas Kedokteran Universitas Lampung. Medulla. 2017;7:157-63. Pioh V, Mewo Y, Berhimpon S. Efektivitas kelompok diskusi tutorial problem based learning di Fakultas Kedokteran Universitas Sam Ratulangi. Jurnal e-Biomedik. 2016;4:1-9. https://doi.org/10.35790/ebm.4.1.2016.12141